The First 1000 Days of Life in Urban Disctrict of Indonesia: A Prevalence and Descriptive Epidemiology - Hashfi Khairuddin; Dwi Pawitra Wulan; Fahdah Hindriana Warsita Putri; Achmad Mubarok Muchdi (Universitas Malahayati Lampung, 2024)
ABSTRACT Children will experience stunting due to insufficient nutrition in the first 1000 days of life. 21.6% of children in Indonesia still suffer from stunting. It is interesting to study how the conditions of one of the most developed places in a country with a prevalence of stunting are still above the global average. This study aims to present a prevalence and descriptive epidemiology of the first 1000 days of life in Cempaka Putih District, Jakarta. This descriptive epidemiology study describes the number of sufferers of pregnant women with anemia or chronic energy deficiency and infants under two years of age who suffer from nutritional deficiencies such as underweight, wasted, or stunting. The data was taken from cohort data from the Cempaka Putih District health center and routine monthly checks at each integrated toddler service post in each Hamlet at the Cempaka Putih District. After that, a mapping is made of the cases in each Hamlet. 14.4% of pregnant women who received antenatal care in the Cempaka Putih sub-district suffered from anemia, while 11.7% suffered from chronic energy deficiency. It was found that 2.8% of infants under two years were underweight/severely underweight, 3.5% were wasted/severely wasted, and 2.4% were stunted/severely stunted. Only 6 out of 30 hamlets have no cases of pregnant women or toddlers with nutritional deficiencies. The number of pregnant women with anemia or chronic energy deficiency and prevalence of infants with underweight, wasted, or stunted in the Cempaka Putih district is much lower than in the provinces of Jakarta and Indonesia. Keywords: Stunting, Prevalence, Urban, 1000 Days of Life